Return Spill-Over Of Green Bond from Various Economic Group Countries During Economic Policy Uncertainty - Andrean Filemon; Zaäfri Ananto Husodo (Green Publisher Indonesia, 2024)
This research analyzes the return spill-over of green bonds issued among several categories of countries and relation of its return spill-over to various global economic conditions. The research employs a time-varying parameter vector autoregression (TVP-VAR) methodol-ogy to account for the return spill-over among countries, and wavelet coherence analysis (WCA) for relation between return spill-over and global economic policy uncertainty (GEPU) index. This study utilizes yield data from green bonds issued from January 2014 to February 2024. This period chosen based on the commencement of green bond issuance in several Emerging Market (EM), Frontier Market (FM) and Least Developed Market (LDM). The findings of this research is the green bonds issued from Developed Market (DM) gives bigger return spill-over effect to the green bonds issued from EM, rather than to FM and to LDM. This spill-over effect from DM to EM raises due to the high GEPU Index, which means the more uncertain the global economics policy, investor rather to safe in stable financial instrument such as green bonds issued in DM and EM.